2017
DOI: 10.21270/archi.v6i10.2249
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Vickers hardness and corrosion behavior of experimental Ti-Mo alloy in dental office bleaching agents

Abstract: At present, titanium and its alloys stand out for their mechanical and biological properties. Vickers hardness and the effect of 15%, 22% and 35% hydrogen peroxide (H2O2) on Ti-10Mo alloy corrosion were evaluated. A conventional double-walled glass cell was used for thermostatization. As reference electrode was used the Ag/AgCl (s)/KClsat and as auxiliary electrode graphite stick. The work electrodes consisted of Ti-10Mo cylinders embedded in polyethylene, with electrical contact by brass wire and silver paint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…For the XRD obtained for the analyzed ternary alloy, intense and major Ti-β peaks were identified. In addition, the crystallographic plane of this Ti-β-phase was also indexed to these minority peaks, which were stabilized with the increase in the amount of Mo and Nb in the nominal composition of the alloys [25]. It was also observed that the Ti-β peaks were shifted towards lower diffraction angles, as illustrated in Figure 5, suggesting that Mo and Nb atoms may have been dissolved in these crystalline structures.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…For the XRD obtained for the analyzed ternary alloy, intense and major Ti-β peaks were identified. In addition, the crystallographic plane of this Ti-β-phase was also indexed to these minority peaks, which were stabilized with the increase in the amount of Mo and Nb in the nominal composition of the alloys [25]. It was also observed that the Ti-β peaks were shifted towards lower diffraction angles, as illustrated in Figure 5, suggesting that Mo and Nb atoms may have been dissolved in these crystalline structures.…”
Section: Resultsmentioning
confidence: 87%
“…Microhardness was evaluated in order to visualize material wear that has impact on prothetic development and aging of the material inside the body [25]. The Vickers microhardness test (HV) was carried out in accordance with ASTM E 384 using a microhardness tester (Shimadzu, Tamboré, Brazil).…”
Section: Microhardness Evaluationmentioning
confidence: 99%